Collaborative Governance: Re-Enactment Share Understanding in the Process of Agricultural Food Management in Karawang Regency - Marvin Angelo Gracino; Evi Priyanti; Dewi Noor Azijah (International Journal of Business, Economics, and Social Development, 2021)
Sustainable Food Agricultural Land Protection is a system and process in planning, developing, utilizing, controlling, and monitoring agricultural land that is determined to be consistently protected in order to produce staple food for national food security. Currently, food agriculture land in Karawang Regency is increasingly under threat along with the rapid development of the industrial sector in the area and threats from the surrounding area. Not only because of the conversion into industrial land, but the existence of factories around it also threatens soil fertility and water quality due to the factory waste itself. The focus in this paper is how the Karawang Regency Government carries out Collaborative Governance in protecting sustainable food agricultural land. In this study, the authors used a qualitative method with a phenomenological approach. The purpose of this research is to explain how to study and analyze the implementation of policies on the protection of sustainable agricultural land with one of the stages of collaborative governance from Ansell and Gash, namely share understanding. The results showed that the Government of Karawang Regency has succeeded in conducting share understanding in collaborative governance well because it has the same goal, namely to create national food security. Openness and interdependence with each other fosters a sense of understanding. However, the community's understanding regarding PLP2B is felt to be lacking because they have not received good socialization from the Karawang Regency Government.